Нина Орлова, Проектная деятельность в обучении русскому языку как иностранному (культурно-переводческий проект "Кухня народов Северного Кавказа". Из опыта международного сотрудничества ВМУ и ПГУ) - Ndiaye, Iwona Anna; Орлова, Нина (Acta Polono-Ruthenica, 2021)
This article deals with the project method as one of the universal modern teaching technologies in literature classes in the audience of foreigners studying Russian. The implementation of the Polish-Russian cultural and translation project “The Cuisine of the Peoples of the North Caucasus” is discussed. Using this particular example, the goals, sequence of actions, forms and results of the didactic process are described, and recommendations are given as regards working with students-philologists.